A Novel Fault Phase Selector for Double-Circuit Transmission Lines - Xing Deng; Xianggen Yin; Zhe Zhang; Xiangping Kong; Cheng Qiu (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
A novel fault phase selector for double-circuit transmission lines is presented. The fault type is determined with the superimposed components and steady state components of fault voltage. According to the determined fault type, auxiliary criteria based on the magnitude and phase difference of fault phase current is applied to judge whether inter-line fault happens or not. If inter-line fault happens, the fault phase is determined by comprehensive criteria based on the comparison of current magnitude and the judgment of impedance direction. The simulation results verify the correction of the proposed phase selector. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1569